A New Light on Non-deductive Argumentation Schemes. - Wohlrapp, Harald (Argumentation, 1998)
T. Govier‘s description of ‘conductive argument‘ and ‘A priori analogy‘ is taken as a start to investigate non-deductive argumentation. It is here argued, that the nature of those types can be better understood when taking up a dynamic view (in addition to the usual structural view). The concepts of ‘frame‘ and ‘position‘ are constructed in order to establish such a twofold approach.